2015
DOI: 10.1111/1758-2229.12344
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen–nematode interaction: Nitrogen supply ofListeria monocytogenesduring growth inCaenorhabditis elegans

Abstract: Listeria monocytogenes is a Gram-positive facultatively intracellular human pathogen. Due to its saprophytic lifestyle, L. monocytogenes is assumed to infect and proliferate within soil organisms such as Caenorhabditis elegans. However, little is known about the nutrient usages and metabolite fluxes in this bacterium-nematode interaction. Here, we established a nematode colonization model for L. monocytogenes and a method for the efficient separation of the pathogen from the nematodal gut. Following (15)N labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…To summarize, L. monocytogenes is able to use multiple N-sources during growth in a defined MM and exhibits a high flexibility with respect to the simultaneous exploitation of alternative N-sources such as ethanolamine and GlcN. The relevance of the utilization of the latter substrates as N-sources by L. monocytogenes during infection, however, remains to be addressed (Buchrieser et al, 2003;Kern et al, 2015). Interestingly, the genes involved in ethanolamine utilization are upregulated during growth of L. monocytogenes in the intestinal tract of mice (Toledo-Arana et al, 2009) and contribute to replication in Caco-2 cells (Joseph et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To summarize, L. monocytogenes is able to use multiple N-sources during growth in a defined MM and exhibits a high flexibility with respect to the simultaneous exploitation of alternative N-sources such as ethanolamine and GlcN. The relevance of the utilization of the latter substrates as N-sources by L. monocytogenes during infection, however, remains to be addressed (Buchrieser et al, 2003;Kern et al, 2015). Interestingly, the genes involved in ethanolamine utilization are upregulated during growth of L. monocytogenes in the intestinal tract of mice (Toledo-Arana et al, 2009) and contribute to replication in Caco-2 cells (Joseph et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A key technology to answer these questions is isotopologue profiling that has been applied to study the carbon metabolism of L. monocytogenes under various conditions by introducing diverse 13 C-labeled tracers (Eisenreich et al, 2006;Eylert et al, 2008;Joseph et al, 2008;Eisenreich et al, 2010;Grubm€ uller et al, 2014). Recently, we used 15 N-isotopologue profiling to demonstrate N-fluxes from Caenorhabditis elegans to L. monocytogenes during infection (Kern et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, isotopolog profiling has proven to be a powerful approach to describe substrate and pathway usages for a number of pathogens including L. pneumophila (Eylert et al, 2010; Schunder et al, 2014; Häuslein et al, 2015; Gillmaier et al, 2016; Kern et al, 2016). The method is based on 13 C-incorporation experiments using completely or selectively 13 C-labeled substrates such as glucose, serine or glycerol.…”
Section: Introductionmentioning
confidence: 99%
“…This auxotrophy reduced the virulence by a factor of ten. However, attenuation based on the histidine and adenine auxotrophy in the Salmonella vaccine strain might be compensated in the worm's intestine through direct uptake of amino acids from the gut, as shown in Kern et al ( 2016 ) for Listeria. Nevertheless, the results showed that the combined attenuation of the Salmonella vaccine strain was sufficient to restore the lifespan of C. elegans to those of worms fed with E. coli OP50.…”
Section: Discussionmentioning
confidence: 99%